Mechanical, Wear, and Fracture Behavior of Titanium Diboride (TiB2) - Cerium Oxide (CeO2) Reinforced Al-6061 Hot-rolled Hybrid Composites (Fracture and Structural Integrity, 2022)
Development of aluminium composites by stircasting technique is an effective method for fabrication of better quality of MMCs. Stircasting technique is one of the most commonly accepted techniques. In this research work, Al6061 / TiB2+CeO2 hybrid MMCs have been fabricated with varying wt. % of TiB2 (2.5%, 5%, 7.5% and 10%) particulates and constant 5% of CeO2 particulates. The monolithic alloy and hybrid composite were hot-rolled at a temperature of 515°C. Whereas, both the monolithic and hot-rolled hybrid composite was subjected to micro-structural study, hardness and tensile test. Optical microscope analysis revealed uniform dispersal of hard particles with in the base matrix in case of both of ascast and hot-rolled composites. Both ascast and hotrolled hybrid composites have shown extensive enhanced mechanical behavior and high wear resistance when compared with monolithic alloy. Though, ductility of the hybrid MMCs decreased with increasing TiB2 and CeO2 content. A tensile and wear fractography outcome shows the internal fractured structure of a tensile and wear specimen which was analysed using a SEM analysis.
Keywords: AMMCs; Hot rolling; Microstructure; Mechanical behavior; Wear behavior; Fracture behavior